Viral Factors in Non-Progression - Wang, Bin (Frontiers in Immunology, 2013)
Research has undergone considerable development in understanding a small subset of human immunodeficiency virus type 1 (HIV-1)-infected, therapy-naive individuals who maintain a favourable course of infection surviving for longer periods of time. Although, viral, host genetic and immunological factors have been analysed in many previous studies in order to delineate mechanisms that contribute to non-progressive HIV disease, there appears to be a no clear cut winner and the non-progressive HIV disease in